Characterization of the Different Subtypes of Immune Cell Infiltration to Aid Immunotherapy - Li, Zhenqing; Mao, Kai; Ding, Bo; Xue, Qun (Frontiers in Cell and Developmental Biology, 2022)
PD-1 ablation or PD-L1 specific monoclonal antibody (mAb) against PD-1 can recruit the accumulation of functional T cells, leading to tumor rejection in microenvironment and significantly improving the prognosis of various cancers. Despite these unprecedented clinical successes, intervention remission rates remain low after treatment, rarely exceeding 40%. The observation of PD-1/L1 blocking in patients is undoubtedly multifactorial, but the infiltrating degree of CD8+T cell may be an important factor for immunotherapeutic resistance. In this study, we proposed two computational algorithms to reveal the immune cell infiltration (ICI) landscape of 1646 lung adenocarcinoma patients. We defined three ICI patterns and the ICI scores were determined by using principal-component analysis. The high ICI score was characterized by high tumor mutation burden (TMB) and cell proliferation-related signaling pathways. Low immune-related genes expression and MYC targets pathways were observed in low ICI score subtypes, indicating T cell suppression, and may be responsible for poor prognosis. The high score demonstrated significant therapeutic advantage and clinical benefits. Our research identified that the ICI scores worked as an effective immunotherapy index, which may provide a promising therapeutic strategies on immune therapeutic for lung adenocarcinoma.